PUNYULUHAN POLA ASUH ANAK DENGAN BAHASA POSITIF PADA IBU-IBU PKK DUSUN PILAHAN, REJOWINANGUN, KOTAGEDE, YOGYAKARTA - Siti Saudah; Syafriyudin Syafriyudin (Dharma: Jurnal Pengabdian Masyarakat, 2021)
The problem faced by parents in society today is the moral degradation of the younger generation. To create a generation that is intelligent, skilled, intellectual, wise, virtuous and pious, proper parenting is needed. Language is a cultural or personality trait that exists within a person, so that with proper parenting, a person will become a civilized person and society and support the process of creating quality human resources. The problem in this paper is How to raise children using "positive language"? This PKM aims to provide counseling related to parenting problems using "Positive Language". This PKM is carried out in PKK RT. 39 RW 12 Pilahan hamlet, Rejowinangun village, Kotagede Yogyakarta district with a total of 30 participants. Extension is delivered by lecture method with the help of audio-visual media. This counseling went smoothly and participants were able to receive the material given actively and enthusiastically while attending the counseling.